FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS TIDUR PASIEN HEMODIALISIS - Arta Marisi Dame; Yuni Shanti Ritonga; Paskah Rina Situmorang; Noradina Noradina; Meriani Siahaan; Bernita Silalahi (Jurnal Ilmiah Keperawatan IMELDA, 2025)
Background: Sleep quality is defined as a state where a person is satisfied with their sleep so that they do not show signs of sleep disorders. Patients undergoing hemodialysis are 25% more likely to experience sleep disorders than normal adults. Objective: This study aims to determine the factors associated with sleep quality in hemodialysis patients. Method: This study is a quantitative study with an analytical survey design through a cross-sectional approach. The sampling technique in this study was accidental sampling. The sample in this study were patients who underwent hemodialysis regularly at least 2 times a week. Data collection used the Pittsburgh Sleep Quality Index (PSQI) questionnaire in Indonesian, a physical activity questionnaire and a Fatigue Severity Scale (FSS) questionnaire with a total of 58 hemodialysis patients at RSU Imelda Pekerja Indonesia. Data analysis used bivariate data analysis with the chi-square test. Results: This study showed that there was no significant relationship between age (p=0.956), gender (p=0.225), employment status (p=0.462), duration of hemodialysis (p=0.559) and sleep quality of hemodialysis patients at Imelda Buruh Indonesia Hospital. There was a significant relationship between comorbidities (p=0.001), smoking habits (p=0.026), coffee consumption (p=0.003), physical activity (p=0.000) and fatigue levels (p=0.000). Conclusion: Lifestyle factors (smoking habits, coffee consumption), comorbidities, physical activity and fatigue levels are related to sleep quality of hemodialysis patients. Suggestion: Future researchers should examine the sleep quality of hemodialysis patients with different methods and research designs.